Effect of Mn content on crystallization behaviors and magnetic properties of FeCoNiBMn high-entropy amorphous alloys - Shaohua Wang; Fang Wang; Yanqin Liang; Hui Jiang; Zhaoyang Li; Shuilin Wu; Chuntao Chang; Shengli Zhu; Zhenduo Cui (Journal of Materials Research and Technology, 2024)
FeCoNi-based high-entropy alloys (HEAAs) attracted much attention because of their good thermodynamic stability, mechanical properties and soft magnetic properties. In this paper, Fe22Co22Ni22B34-xMnx (x = 6–22 at%) HEAAs were designed and the effects of Mn on the crystallization behaviors, magnetic performance, and mechanical property were investigated. The crystallization behaviors of the FeCoNiBMn HEAAs are: 1) 12–16 at% Mn: am → am’ + M23B6 → M23B6 + fcc; 2) 18 at% Mn: am → am’ + bcc + M23B6 → bcc + M23B6 → fcc + M23B6; and 3) 20–22 at% Mn: am → am’ + bcc → bcc + M23B6 → fcc + M23B6. Two parameters ΩA and VEC are proposed to predict the primary precipitates of FeCoNi-based HEAAs. All as-spun ribbons exhibit excellent soft magnetic properties with a very low coercivity (Hc) of less than 1.5 A/m and a maximum saturation magnetization (Bs) of 0.82 T. The 14 at% Mn alloy exhibits very low Hc of less than 4 A/m even after complete crystallization. Magnetic properties and Vickers hardness of crystalline ribbons are closely related to crystallization behaviors.